NATURE — THE PRICELESS WEALTH OF HUMANITY - Murodullayev Botirjon (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, reflects on the extraordinary beauty and vital importance of nature in human life. Drawing on personal observations from his hometown of Toʻraqoʻrgʻon, the author highlights the environmental challenges caused by human carelessness and calls on young people to take practical steps to protect and preserve the natural world around them.